In Search of "Industrial Harmony": The Process of Labour Law Reform in Manitoba, 1984 - Black, Errol (Relations industrielles / Industrial Relations, 1985)
This paper examines the roots of the controversy over industrial relations within Manitoba NDP, looks at the process which the government initiated as a means of delivering its commitments to organized labour and outlines the conditions by which the business class in Manitoba forced the government to retreat.